2003
DOI: 10.1021/bi034252z
|View full text |Cite
|
Sign up to set email alerts
|

Proflavine Acts as a Rev Inhibitor by Targeting the High-Affinity Rev Binding Site of the Rev Responsive Element of HIV-1

Abstract: Rev is an essential regulatory HIV-1 protein that binds the Rev responsive element (RRE) within the env gene of the HIV-1 RNA genome, activating the switch between viral latency and active viral replication. Previously, we have shown that selective incorporation of the fluorescent probe 2-aminopurine (2-AP) into a truncated form of the RRE sequence (RRE-IIB) allowed the binding of an arginine-rich peptide derived from Rev and aminoglycosides to be characterized directly by fluorescence methods. Using these flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 57 publications
0
47
0
2
Order By: Relevance
“…On the basis of previous studies that identified base positions in TAR that are essential for high-affinity Tat peptide/ argininamide binding (Weeks et al 1990;Crothers 1991, 1992) and structural investigations that indicated large conformational changes in the bulge of TAR upon interaction with argininamide/Tat peptide (Puglisi et al 1992;Aboulela et al 1995;Long and Crothers 1999), it was reasoned that substitution of 2-AP at these bulge positions would be nonperturbing and provide sensitive probes of ligand interactions with TAR. 2-AP fluorescence methods have been similarly used to characterize binding of small molecule inhibitors and Rev peptide to the HIV-1 rev responsive element (RRE; Lacourciere et al 2000;DeJong et al 2003), aminoglycoside binding to prokaryotic and eukaryotic ribosomal RNA sequences (Kaul et al 2004), and inhibition of hammerhead ribozymes (Kirk et al 2001). In addition, 2-AP fluorescence has been applied to characterize RNA conformational changes associated with peptide binding (Austin et al 2003;Barrick and Roberts 2003), chaperone mediate RNA refolding (Rist and Marino 2002), and ribozyme cleavage (Harris et al 2002;Jeong et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous studies that identified base positions in TAR that are essential for high-affinity Tat peptide/ argininamide binding (Weeks et al 1990;Crothers 1991, 1992) and structural investigations that indicated large conformational changes in the bulge of TAR upon interaction with argininamide/Tat peptide (Puglisi et al 1992;Aboulela et al 1995;Long and Crothers 1999), it was reasoned that substitution of 2-AP at these bulge positions would be nonperturbing and provide sensitive probes of ligand interactions with TAR. 2-AP fluorescence methods have been similarly used to characterize binding of small molecule inhibitors and Rev peptide to the HIV-1 rev responsive element (RRE; Lacourciere et al 2000;DeJong et al 2003), aminoglycoside binding to prokaryotic and eukaryotic ribosomal RNA sequences (Kaul et al 2004), and inhibition of hammerhead ribozymes (Kirk et al 2001). In addition, 2-AP fluorescence has been applied to characterize RNA conformational changes associated with peptide binding (Austin et al 2003;Barrick and Roberts 2003), chaperone mediate RNA refolding (Rist and Marino 2002), and ribozyme cleavage (Harris et al 2002;Jeong et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We validated the assay using small interfering RNA (siRNA) knockdowns, targeting the Tat activation domain, and with 3,6-diaminoacridine, a known small-molecule inhibitor of the Rev-RRE interaction that served as a positive control (see Fig. S1 in the supplemental material) (34).…”
Section: Resultsmentioning
confidence: 99%
“…Two compounds, PRF and K-37 were used to prove efficacy of the assay. PRF interferes with Rev-RRE interaction by competing directly with the Rev binding site on RRE [8] whereas K-37 is a fluoroquinoline derivative, a class of small RNA binding molecule that inhibits Tat and other RNA dependent trans-activations [1,17]. Since, the drugs used in the study did not show any cellular cytotoxicity or alteration in the expression of the transactivator but significantly inhibited reporter gene expression, it was confirmed that the reporter expression down regulation was specifically due to interference of Rev-RRE interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were separated on a 15 % SDS-PAGE gel, transferred to PVDF membrane (Immobilon-P; Millipore, USA). The membranes were blocked (5 % non fat dry milk in Tris-buffered saline with 0.1 % Tween 20) for 1 h followed by overnight incubation at 4°C with HIV-1 Rev antibody [8,28]. Membrane was washed and incubated with HRPO conjugated secondary Fig.…”
Section: Luciferase Assaymentioning
confidence: 99%